First conference of headquarters and regional members of the Careers Committee held on Thursday 22 April 1982 proceedings. (Institution of Civil Engineers, 1982)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 22 April 1982.